Pengaruh Operating Profit Margin, Cash Holding, Bonus Plan, dan Income Tax terhadap Perataan Laba - Inggit Pangesti Nirmanggi; Muhamad Muslih (Universitas Pendidikan Ganesha, 2020)
Income smoothing is one part of earnings management that aims to reduce or increase the profit to be reported, so that earnings will look stable from the previous period or the period thereafter. Stakeholders need to know the factors that can influence income smoothing so they are not wrong in making decisions. This study aims to determine the effect of operating profit margin, cash holding, bonus plan, and income tax variables on income smoothing in mining sector companies listed on the Indonesia Stock Exchange in 2013-2018 as many as 36 samples. Secondary data collection techniques and analysis used logistic regression (SPSS 22 software). Based on the results of the study, operating profit margins, cash holding, bonus plan, and income tax simultaneously have a significant effect on income smoothing. Partially, operating profit margin, bonus plan, and income tax have no significant effect on income smoothing. While cash holding has a positive and significant effect on income smoothing.